ANALISIS PRAKTIK WIRAUSAHA PADA USAHA MERCON TANTAN SEBAGAI UMKM KULINER LOKAL - Anisa Auliya; Risti Indah Sari F; Suasa Suasa; Dandan Haryono; Nurhayati Hamid (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This study aims to analyze entrepreneurial practices in local culinary Micro, Small, and Medium Enterprises (MSMEs), namely Mercon Tantan, amidst the rapid development of the food industry in Indonesia. MSMEs are the main foundation of the national economy with a significant contribution to job creation and economic growth. Mercon Tantan is a manifestation of innovation that raises the theme of the typical spicy dish "mercon," successfully attracting attention, especially the younger generation, through menu variations, levels of spiciness, and intense flavor profiles. The results of interviews indicate that the main challenges faced by Mercon Tantan are the rampant competition with similar vendors and the need for innovation to meet the public's desire for more contemporary products.